Facile and Scalable Route to Access Rare Deoxy Amino Sugars for Nonulosonic Acid Aldolase Biosynthesis - Zhou, Yixuan; Liao, Kuo-Shiang; Li, Shiou-Ting; Wu, Chung-Yi (Frontiers in Chemistry, 2022)
We presented a facile and scalable route for the synthesis of di-azido sugars via one-pot double inversion of the mono-benzoyl sugars by TBAN3 and studied the dependency pattern between solvent and protecting group as well as the configuration of the neighboring and leaving groups. We found supramolecular control effect could facilitate nitrite-mediated carbohydrate epimerization next to azido groups. Moreover, we developed a chemical synthetic strategy for Pse precursor (11 steps in 49%). Furthermore, we discussed the configuration of NulO precursors for specificity of PseI and PmNanA enzymatic synthesis, permitting us to synthesize new NulO derivatives for accessing Pse isomer.